Using power series method solve the equation
y''+9y=0
"y = \\sum\\limits_{n=0}^{+\\infty} c_n x^n" ,
"y'' = \\sum\\limits_{n=0}^{+\\infty} n(n-1)c_n x^{n-2} = \\sum\\limits_{n=0}^{+\\infty} (n+2)(n+1)c_{n+2} x^{n}"
"y'' + 9y = \\sum\\limits_{n=0}^{+\\infty} ((n+2)(n+1)c_{n+2}+9c_n) x^{n} = 0"
"(n+2)(n+1)c_{n+2}+9c_n = 0"
"c_{n+2}=\\frac{-9}{(n+2)(n+1)}c_n"
"c_{2n} = \\frac{(-9)^n}{(2n)!}c_0"
"c_{2n+1} = \\frac{(-9)^n}{(2n+1)!}c_1"
"y=\\sum\\limits_{n=0}^{+\\infty} \\frac{(-9)^n}{(2n)!}c_0x^n + \\sum\\limits_{n=0}^{+\\infty} \\frac{(-9)^n}{(2n+1)!}c_1 x^n"
"y= c_0\\cos{3x} + c_1\\sin{3x}"
Comments
Leave a comment